2016
DOI: 10.1111/ceo.12696
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic retinopathy: global prevalence, major risk factors, screening practices and public health challenges: a review

Abstract: Diabetes retinopathy (DR) is a leading cause of vision loss in middle-aged and elderly people globally. Early detection and prompt treatment allow prevention of diabetes-related visual impairment. Patients with diabetes require regular follow-up with primary care physicians to optimize their glycaemic, blood pressure and lipid control to prevent development and progression of DR and other diabetes-related complications. Other risk factors of DR include higher body mass index, puberty and pregnancy, and catarac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
528
1
19

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 778 publications
(620 citation statements)
references
References 190 publications
13
528
1
19
Order By: Relevance
“…Similar findings have been reported in studies from China, Finland, Jordan and Saudi Arabia [9,23,24,28,36]. Hypertension has a strong association with DR (P-value 0.0001), and this was well documented in most of the other studies [24,32,33,37,38]. Like other studies, smoking was not associated with DR (P-value 0.992) [5,9,11,24,39].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Similar findings have been reported in studies from China, Finland, Jordan and Saudi Arabia [9,23,24,28,36]. Hypertension has a strong association with DR (P-value 0.0001), and this was well documented in most of the other studies [24,32,33,37,38]. Like other studies, smoking was not associated with DR (P-value 0.992) [5,9,11,24,39].…”
Section: Discussionsupporting
confidence: 86%
“…Regarding association of obesity with diabetic retinopathy, this study found no significant association, since the relative risk (RR) of BMI (less than 30/more than 30) was 0.615 (95% CI 0.334-1.130). Although a positive correlation of obesity with DR has been found in some studies [3,9,24,[32][33][34], it was found to be protective in another studies [9)]. Controlling blood sugar is a protective factor [5,8,11,32,33,35], and this association was proven in this study.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…1,2 Diabetic retinopathy, a microvascular complication of diabetes 3 associated with various risk factors including poor glycemic control, 3 is a leading cause of acquired vision loss in adults, 4,5 and in 2010 was attributed to 2.6% of global blindness. 6 Anatomical and biochemical changes resulting from retinopathy may lead to diabetic macular edema (DME) in up to a third of patients with diabetes 7,8 and is characterized clinically by swelling of the macula due to increased permeability of blood vessels.…”
mentioning
confidence: 99%